“I have decreed not to sing in my cage”. Melancholy at Court from Castiglione to Shakespeare’s “Much Ado About Nothing” - Ragni, Cristiano (SigMa - Rivista di Letterature comparate, Teatro e Arti dello spettacolo, 2021)
In light of the well-established presence of Castiglione’s The Book of the Courtier in Shakespeare’s Much Ado About Nothing, I will focus on the villain of the play, Don John, and emphasise the hitherto unacknowledged similarities between his character and the melancholic courtiers against whom Castiglione had warned in his work. In so doing, I will underscore how Shakespeare did not limit to a simplistic construct of imitation and adaptation of his Italian model, but proved to be well aware of the contemporary debates surrounding the spreading and the dangerous effects of melancholy.